The Impact of Early Diagnosis and Therapy on the Development of Children with Autism Spectrum Disorders - Teliti, Adisa; Zalli, Eneida (International Journal of Child Health and Nutrition, 2026)
Background: Neurodevelopmental disorders, including autism spectrum disorders (ASD), are increasingly diagnosed in children, but low awareness, delays in diagnosis, and poor service coordination complicate therapy and negatively affect family quality of life. Objective: This study aimed to assess the importance of early detection of ASD and the role of therapeutic interventions in improving child development and family well-being. Methods: Using a qualitative approach, the study involved interviews with 20 pairs of parents of children with ASD and thematic analysis, considering gender, age, and behavioral characteristics, supplemented by the Parental Stress Scale. Results: Early diagnosis (before age 3, 60%) was associated with faster progress compared to late diagnosis. In the early diagnosis group, behavioral therapy, sensory integration, and speech therapy led to improvements in non-verbal communication, reduced sensory hypersensitivity, and decreased aggression. In the late-diagnosis group, with greater use of behavioral therapy and individual education plans, progress was slower, with improvements in speech, reduced aggression, and less social isolation. Parents reported reduced anxiety and improved family relationships, especially in early-diagnosis cases. Barriers included delays in diagnosis (18-24 months), stigma, and inadequate infrastructure. Conclusion: The findings highlight the effectiveness of early intervention and the need for standardized diagnostic procedures, parent education programs, professional training, and improved infrastructure to support families raising children with ASD. These results can guide intersectoral cooperation, policy development, and support strategies for families.